Anesthetic Management for Incomplete Atrioventricular Septal Defect - Bhimo Priambodo; Bhirowo Yudo Pratomo; Juni Kurniawaty (Perhimpunan Dokter Spesialis Anestesiologi dan Terapi Intensif, 2026)
Background: Atrioventricular septal defect (AVSD) is a congenital heart anomaly that arises from the incomplete fusion of the endocardial cushions, resulting in communication between the atria and ventricles and abnormal development of the atrioventricular valves. Incomplete AVSD accounts for a smaller proportion of congenital heart defects but presents significant challenges in both surgical and anesthetic management due to complex pathophysiology and perioperative risks. This study to report and discuss the anesthetic management of a pediatric patient with incomplete AVSD undergoing surgical repair.Case: We report the case of a 7-year-old boy with incomplete AVSD who underwent surgical closure and mitral valve cleft repair. Preoperative evaluation included echocardiography and cardiac catheterization. General anesthesia was induced with fentanyl, propofol, and sevoflurane, and maintained during cardiopulmonary bypass (CPB). Intraoperative transesophageal echocardiography (TEE) confirmed effective repair. Postoperatively, the patient experienced transient arrhythmia that resolved with pacing and was successfully extubated on the first postoperative day without complications.Discussion: Children with congenital heart disease (CHD) are at higher risk of morbidity and mortality due to the complex physiological derangements caused by the defects. Anesthetic management in AVSD depends on the degree of left-to-right shunting and the presence and severity of pulmonary vascular hypertension. Important considerations include neonatal and pediatric anesthesia principles, congenital cardiac anatomy and physiology, CPB techniques, and potential postoperative complications.Conclusion: Anesthetic management in incomplete AVSD requires a comprehensive understanding of pediatric CHD, perioperative monitoring, and CPB protocols. Multidisciplinary collaboration and meticulous perioperative planning are crucial in improving outcomes and minimizing complications in pediatric cardiac surgery.